(3GdEHJgGL aj GdcdGe Ydi GdESQGA hGdeYQGLs - (3GdZjWj , eMeO Hf CMeO Hf Ydj GdScfOQj GdTGaYj, fLe GdOjf CHh GdehGgH,J (B981 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje (B:" (3SHMGf GdPi CSQi HYHOg djdkG ef GdeSLO GdMQGe Edi GdeSLO GdCbUi GdPi HGQcfG Mhdg dfQjg ef BjGJfG Efg gh GdSejY GdHUjQ (B" (3hSfJcde Ef TGA Gddg JYGdi Ydi HYV ahGFO gPg GdBjI GdcQjeI s
(3BNQgG (B:s
(3Yf CfS bGd(B: (3cGf QShd Gddg Udi Gddg Ydjg hSde EPG eQ ai WQjb ef WQb GdeOjfI hSde ef gPG GdWQjb hGdCFeI GdeLJgOjf hSGFQ YdeGA GdeSdejf Bejf s
(3GdfSNI HgG MhGTs
(3hbO JedcgG YHO GdhGMO Hf YHO Gddg Hf YHO GdhGMO GdWQGHdSis
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B293s
Keywords: (3GdMOjK h GdeUWdMs